The Effect of Translation Techniques on the Quality Assessment of TikTok Account Captions @IqraaMedia - Pratiwi, Ameliya; Mubarak, Muhammad Zaky; Maulani, Abdullah; Suparno, Darsita (Study Program of Arabic Language Teaching, 2025)
This study investigates the impact of translation techniques on the quality of automatic Arabic–Indonesian translations in TikTok captions from the account @IqraaMedia. The objectives of this research are to identify the translation techniques employed and to evaluate translation quality in terms of accuracy, acceptability, and readability. This study adopts a descriptive qualitative approach using text analysis. The data consist of 25 Arabic TikTok captions containing Islamic preaching content, along with their automatically generated Indonesian translations. The data were purposively selected based on the relevance and completeness of the translations and collected through documentation, observation, and recording captions from the TikTok platform. Data analysis was conducted in three stages: identifying structural and semantic shifts between source and target texts; classifying translation techniques using Molina and Albir’s framework; and assessing translation quality using Nababan et al.’s model, rated on a 3-point scale (1–3) by three expert raters. The findings reveal seven translation techniques, with transposition as the most frequently used (32.39%), followed by established equivalence and literal translation (23.94% each). Translation quality assessment yielded average scores of 2.12 for accuracy, 1.84 for acceptability, and 1.80 for readability, indicating moderate overall quality. The results suggest that automatic translations generally convey the main message but often lack naturalness, cultural appropriateness, and clarity, particularly in translating religious terms. This study concludes that while automatic translation facilitates access to Arabic Islamic content on social media, improvements are required to enhance translation quality for effective multilingual religious communication.